Ascariasis in a child with recurrent gastrointestinal hemorrhage: case report and literature review - Wang, Tao; Tan, Qingti; Wu, Qing; Chen, Yuetong; Zhou, Qin; Luo, Xiaoli (Frontiers in Pediatrics, 2025)
BackgroundAscaris lumbricoides is one of the most common soil-transmitted helminth infections worldwide, particularly in tropical and subtropical regions with poor sanitation. While most cases are asymptomatic, heavy infections can lead to serious complications including intestinal obstruction, biliary colic, and pancreatitis. This article reports a case of melena in a 4-year-old child associated with ascariasis and explores the potential pathological mechanisms and management strategies through a comprehensive literature review.Case descriptionA 4-year-old boy was admitted with a one-month history of cough, lethargy for 4 days, and coma lasting 10 h. He had been diagnosed with septic shock, severe pneumonia, acute respiratory failure, and multiple organ dysfunction syndrome (MODS) at a local hospital, where he received endotracheal intubation with mechanical ventilation, aggressive fluid resuscitation, and antimicrobial therapy before being transferred to our institution for further management. During hospitalization, he experienced recurrent melena, which required blood product transfusion to correct anemia. Further investigations eventually identified ascariasis as a potential underlying contributing factor. Melena in this patient was likely related to septic shock-induced coagulopathy or mucosal ischemia, rather than direct Ascaris injury. The patient was treated with albendazole, and ultimately made a full recovery and was discharged successfully.ConclusionsAscaris lumbricoides infection represents a rare yet critical associated factor in septic shock complicated by severe gastrointestinal bleeding in children. This case report and literature review demonstrate that successful management hinges on early identification of the parasitic infection coupled with timely anthelmintic therapy following hemodynamic stabilization. However, the severe clinical manifestations are often directly caused by secondary bacterial infections. Clinicians, particularly those in endemic regions, require heightened vigilance for this potential complication.